2022
DOI: 10.3389/fpls.2022.928092
|View full text |Cite
|
Sign up to set email alerts
|

Optimal exogenous calcium alleviates the damage of Snow-melting agent to Salix matsudana seedlings

Abstract: As the main component of snowmelt agents, NaCl is widely used in northern winters and significantly impacts the expected growth of garden plants in north China. Salix matsudana is also faced with salt stress caused by snowmelt, which seriously affects its development as the main tree species in the northern landscape. However, how exogenous calcium alleviates salt stress in Salix matsudana is not yet clear. In this study, the indicators of growth indices, photosynthetic characteristics and stress resistance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…(2021) found that exogenous Ca 2+ promoted the function of K + channels and its uptake through the root plasma membrane, reduced the permeability of the plasma membrane for Na + pumping so to decrease the accumulation of passive Na + inward flow. Li et al. (2022a) indicated that the exogenous Ca 2+ treatment could increase the maximum photochemical efficiency (Fv/Fm) under salt stress in Mongolian pines and 10 mM exogenous Ca 2+ could promote the growth of Salix matsudana Koidz seedlings and increase their stomatal conductance, transpiration rate (Tr) and net photosynthetic rate.…”
Section: Advances In Application Of Exogenous Ca 2+ ...mentioning
confidence: 99%
See 3 more Smart Citations
“…(2021) found that exogenous Ca 2+ promoted the function of K + channels and its uptake through the root plasma membrane, reduced the permeability of the plasma membrane for Na + pumping so to decrease the accumulation of passive Na + inward flow. Li et al. (2022a) indicated that the exogenous Ca 2+ treatment could increase the maximum photochemical efficiency (Fv/Fm) under salt stress in Mongolian pines and 10 mM exogenous Ca 2+ could promote the growth of Salix matsudana Koidz seedlings and increase their stomatal conductance, transpiration rate (Tr) and net photosynthetic rate.…”
Section: Advances In Application Of Exogenous Ca 2+ ...mentioning
confidence: 99%
“…Ca 2+ plays an important role in plant stomatal regulation as the second messenger in coupled with external signals in plant cells. Appropriate amount of Ca 2+ can make plants adapt to abiotic stresses such as drought and salinity quickly by adjusting their stomatal opening/closing, optimizing their gas exchange, and improving their photosynthetic efficiency ( Li et al., 2012 ; Li et al., 2022a ). These plant adjustments and adaptations by using exogenous Ca 2+ could be achieved through reshape, rearrangement and configuration of stomata during their differentiation and development for more efficient of gas exchange and water utilization ( Zhang et al., 2019a ).…”
Section: Mechanisms Of the Role Of Exogenous Ca 2+ ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive use of snowmelting agents results in a rise in pH levels and the accumulation of toxic concentrations in plant tissues, which can lead to saline-alkali stress and an increased osmotic pressure [3]. This factor has a negative impact on the seed germination and photosynthetic response of plants [4]. In order to enhance the promotion of saline-alkali tolerance cultivars, it is crucial to investigate the mechanisms of plant germination and physiological response under saline-alkali stress.…”
Section: Introductionmentioning
confidence: 99%